2008
DOI: 10.1158/0008-5472.can-07-2454
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Lymphedema: An Urgent Need for Adequate Animal Models

Abstract: In cancer patients, the removal of tumor-draining lymph nodes during tumor resection can lead to acquired lymphedema. This disease, which is characterized by tissue swelling and increased risk of infection due to restricted lymph flow, lacks an effective treatment. Limitations to the design and conduct of randomized trials to date have limited the evaluation of proposed surgical techniques. As a result, animal models have provided an important research base. This review summarizes work in canine, rabbit, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 18 publications
1
31
0
1
Order By: Relevance
“…The removal of the LN damages the axillary lymphatic system and impairs lymph drainage. As described by Hadamitzky and Pabst, adequate models to study lymphedema development are missing, although there is an urgent need for such animal models [1]. In the present study we showed that lymphadenectomy results in a development of lymph vessel collaterals and dermal backflow in minipigs 8 months later.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The removal of the LN damages the axillary lymphatic system and impairs lymph drainage. As described by Hadamitzky and Pabst, adequate models to study lymphedema development are missing, although there is an urgent need for such animal models [1]. In the present study we showed that lymphadenectomy results in a development of lymph vessel collaterals and dermal backflow in minipigs 8 months later.…”
Section: Discussionsupporting
confidence: 67%
“…On the way through the body the lymph fluid is screened for foreign agents and particles are filtered in the various LN before leaving the lymph vessel and entering the venous system. The pathophysiology of lymphedema development is very complex and not entirely clear [1]. Surgical removal of LN often leads to an impaired lymph flow, because of the damage to the lymphatic network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of large animal models that better recapitulate conditions in human lymphedema has limited experimental research of lymphedema. 28 Previously used canine models were complex and would be considered unethical today. We present here a novel large animal model of lymphatic vessel damage and lymph node transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Many surgical methods with curative aims have been proposed, but no long lasting effective methods have been established. Recently, it has been summarized that adequate animal models to study lymphedema development and treatment are missing, although there is an urgent need for such models (Hadamitzky and Pabst, 2008).…”
mentioning
confidence: 99%